Composition Control of the CSTC Packed-Type Binary Distillation Column - Malik, Asaad Abdallah Yousuf (1999)
The economic performance of most processes and certainly their safety and operability depend to a large extend on how well they are controlled. That is why finding control means for the complicated Binary Distillation Column process has been attracting the efforts of many researchers and scientists interested in modeling, simulating and designing controls for the process. The CSTC binary distillation column in the form of six DE's has been studied. Simulations have been carried out to validate the model. Further testing on the Open Loop and Closed-Loop was done. The model was formulated in the matrix form and converted to the error coordinate form in order to apply the On-line Riccati control method, which has been successfully implemented and found to be very satisfactory.